2011
DOI: 10.1074/jbc.m111.277681
|View full text |Cite
|
Sign up to set email alerts
|

Functional Organization of Golgi N- and O-Glycosylation Pathways Involves pH-dependent Complex Formation That Is Impaired in Cancer Cells

Abstract: Background: Glycans are synthesized in the Golgi by sequentially acting glycosyltransferases, but it is not known how their functions are coordinated in live cells. Results: N-and O-glycosyltransferases form enzymatically active homo-and/or heteromeric complexes. Conclusion: Glycosyltransferases function as physically distinct enzyme complexes rather than single enzymes. Significance: The results help understand the overall functioning of the Golgi glycosylation pathways both in health and disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
137
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(143 citation statements)
references
References 40 publications
4
137
0
Order By: Relevance
“…It was reported that GalT-I (β-1,4-galactosyltransferase I) and ST6Gal-I (α-2,6-sialyltransferase I) form a complex that increases their enzymatic activity, suggesting that these two N-glycosyltransferases act cooperatively in N-glycan synthesis. 31 Additionally, we noticed that both galactosylation and sialylation of IgG1 tend to negatively correlate with the level of core fucosylation. IgG galactosylation and fucosylation changes going in different directions have been previously described for juvenile chronic arthritis and rheumatoid arthritis.…”
Section: ■ Discussionmentioning
confidence: 93%
“…It was reported that GalT-I (β-1,4-galactosyltransferase I) and ST6Gal-I (α-2,6-sialyltransferase I) form a complex that increases their enzymatic activity, suggesting that these two N-glycosyltransferases act cooperatively in N-glycan synthesis. 31 Additionally, we noticed that both galactosylation and sialylation of IgG1 tend to negatively correlate with the level of core fucosylation. IgG galactosylation and fucosylation changes going in different directions have been previously described for juvenile chronic arthritis and rheumatoid arthritis.…”
Section: ■ Discussionmentioning
confidence: 93%
“…monomeric Venus (mVen), HA (YPYDVPDYA), or Myc (EQ-KLISEEDL) tag (34). Thus, the constructs for flow cytometric FRET had the tags in the C terminus of the HASs.…”
Section: Methodsmentioning
confidence: 99%
“…Immunofluorescence Microscopy and FRET Flow Cytometry-COS7, COS1, HeLa, and MCF7 cells were cultivated in DMEM as described elsewhere (34,35). One day after plating, the cells were transfected using 0.5 g of each plasmid cDNA and the FuGENE 6 TM transfection reagent (Roche Applied Science).…”
Section: Plasmids For the Microscopic Fret Analyses And Co-immunoprecmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also possible that the kinetics of STn biosynthesis by ST6GalNAc-I is slower and takes more time to show an effect in STn expression. Alternative possibilities for aberrant STn expression in cancer contexts include mutations or promoter methylation of the molecular chaperone Cosmc, 38,39 aberrant localization of glycosyltransferases in the ER/Golgi, 40,41 or the activity of another sialyltransferase from the same sub-family as ST6GalNAc-I-ST6GalNAc-II 4 -have been demonstrated. This enzyme, ST6GalNAc-II, was also shown to have some specificity in vitro for GalNAc substrates O-linked to proteins (Tn antigen).…”
Section: Cdx2 Regulates St6galnac-i In Intestinal Metaplasia R Pinto mentioning
confidence: 99%